Formulasi dan Uji Stabilitas Krim Tabir Surya Mengandung Titanium Dioksida (TiO2) dengan Variasi Emulgator: Formulation and Stability Test Sunscreen Cream Containing Titanium Dioxide (TiO2) With Emulgator Variations - Rizky Dwi Yulianti; Siti Mardiyanti (Jurnal Farmasi dan Farmakoinformatika, 2025)
The use of sunscreen creams can protect the function of human skin structures from the negative effects of UV rays. This study aims to formulate sunscreen cream preparations with variations of polysorbate and sorbitan emulgators to determine the physical characteristics of cream preparations and determine the stability of sunscreen cream preparations containing titanium dioxide (TiO2) to SPF (Sun Protection Factor) values. This research uses laboratory experimental methods. The active ingredient used is TiO2, which is a physical blocker by reflecting UV radiation. Polysorbate and sorbitan are the emulgator combinations used in this study. Sunscreen cream preparations were formulated into four formulas by combining and varying the concentration of polysorbate and sorbitan emulgators. FI contained polysorbate 60 (3%) and sorbitan 60 (2%), FII polysorbate 80 (2.5%) and sorbitan 80 (2.5%), FIII polysorbate 60 (2.75%) and sorbitan 80 (2.25%), and FIV polysorbate 80 (3.25%) and sorbitan 60 (1.75%). Furthermore, the preparations were evaluated and tested for stability (cycling test,) as well as effectiveness determination tests (SPF, and %TE). The results showed that different combinations and variations in the concentration of polysorbate and sorbitan emulgators in the four formulas had an influence on the physical characteristics and stability of the preparation. And the results of the determination of the effectiveness of sunscreen cream have an influence of UV exposure on the in vitro effectiveness of sunscreen cream (SPF, and %TE).